Relations of body weight status in early adulthood and weight changes until middle age with metabolic syndrome in the Chinese population - Zhao, Liancheng; Liu, Huanhuan; Zhou, Long; Li, Ying; Guo, Min; Wu, Yangfeng (International Journal Of Community Medicine And Public Health, 2017)
Background: The evidences for the relationship between long-term weight gain and metabolic syndrome (MetS) in Chinese population were limited. Therefore, this study aims to explore the association of body weight status in early adulthood and weight changes with MetS. Methods: Data from China Multicenter Collaborative Study of Cardiovascular Epidemiology including 12808 participants aged 35–59 were used. Participants were surveyed for cardiovascular risk factors and a self-reported weight at age 25, which was defined as early adulthood. Weight change was calculated as the difference between baseline weight and early adulthood weight. MetS was defined according to AHA/NHLBI definition in 2009. Multivariate logistic regression model was used to examine the association between early adulthood weight status, weight change and MetS. Results: Mean age of participants was 46.7 years, including 6134 men and 6674 women. The overall prevalence of MetS was 21.8%. After adjusted for age, sex and other confounding factors, both BMI at 25 age and weight gain were positively associated with the risk of MetS. Being overweight (BMI, 24–27.9 kg m-2) or obese (BMI ≥28 kg m-2) at early adulthood was related to an increased risk of MetS, the odds ratio (OR) and 95%confidence interval (CI) was 3.24 (2.82–3.72) and 13.31 (8.72–20.31). In addition, weight gain was also associated with higher risk of MetS (P for trend<0.01). Conclusions: Overweight and obesity in early adulthood and weight gain were both independently related to an increased risk of MetS in the middle-aged Chinese men and women.